Seismic and energy upgrading of existing buildings—full-scale testing of retrofitted masonry-infilled RC frames - Chrysostomou, Christis; Votsis, Renos; Kyriakides, Nicholas; Illampas, Rogiros; Filippou, Christiana A.; Bousias, Stathis N. (My University, 2023)
Taking into consideration the seismic vulnerability and the poor energy performance of the European building stock, and the increasing socio-economic and environmental need for integrating seismic upgrading with energy efficiency improvement, an experimental study involving the lateral load testing of full-scale one-story one-bay masonry infilled RC frames and load-bearing masonry walls was carried out in the framework of the SupERB research project aiming to investigate the efficiency of integrated seismic and energy upgrading systems. The integrated approach is based on the use of textile reinforced mortar (TRM) overlays combined either with traditional thermal insulation (extruded polystyrene, XPS) or with thermally efficient mortar incorporating phase change material (PCMs). The proposed integrated approach can be applied on the exterior face of the structure, so as to facilitate its application in real structures in the easiest possible way and with minimum disturbance to the inhabitants of the buildings. In this paper, only the structural performance of masonry-infilled RC frames retrofitted with the proposed integrated approach is presented, while the energy benefits will be presented in a separate paper. Thus, in this paper, the structural performance of an integrated seismic and energy upgrading approach was assessed through five full-scale one-story one-bay masonry infilled RC frames that were retrofitted with different schemes of TRM combined with thermal insulation materials subjected to in-plane displacement-controlled cyclic loading. The following parameters were investigated experimentally: the number of TRM overlays (one or two layers of TRM combined with thermal insulation), the use of thermally efficient PCM-enhanced TRM layer in contrast to the use of conventional XPS insulation, and different retrofitting configurations (placement of the TRM in a sandwich form over and/or under the novel or the traditional insulation). From the results obtained in this study, it can be concluded that all energy and seismic upgrading systems examined have a positive impact on the response of the structural system to cyclic loading, with the ones with two layers of TRM having a better performance compared to the ones with one layer of TRM and all of them a better performance than the control specimen. The use of two layers of TRM cancels the drawback of infilled frames, which at very small drifts they reach their maximum capacity and after that they rapidly fall to the capacity of the bare frame, providing capacities above 80% of their peak capacity for drifts up to 2%. In all the tests the TRM whether it was combined with XPS or included PCMs contributed to a better distribution of the cracks in the infill and delayed premature brittle failures. The presence of the TRM had also the advantage that it remained intact throughout the tests preventing the fall of debris out of the plane of the infilled frame, both in the retrofitted and unretrofitted sides.